Production Testing of One-Day Chikens by Untreated Palm Oil Weever Combustion in Gbadolite, the Democratic Republic of Congo - Molongo Mokondande Médard; Idikodingo Anzinzoniwa Faustin; Ambwa Lokula Junior; Ngalakpa Héritier; Ngbolua Koto-te-Nyiwa Jean-Paul; Muhammad Ridwan; Bondombe Gorges-Willy (Britain International of Exact Sciences (BIoEx) Journal, 2023)
This study was conducted in Gbado-Lite; therefore, it had the objective of producing one-day chickens by palm oil weever combustion. The method adopted for this investigation consisted of constructing an incubator using raffia fibers and using the heat offered by the live combustion of palm oil; the eggs were classified in 3 blocks following the rows on a sieve. This source of energy has achieved a temperature threshold of 37.5 to 39.3 ° C, the recommended temperature for artificial incubation; Hatching rate of 88.9 to 93.5% was recorded, a rate close to the natural incubation. This study has a great socio-economic value because with local inputs, chicks are produced in order to be self-sufficient in meat feed.